Wide identification of chemical constituents in fermented licorice and explore its efficacy of anti-neurodegeneration by combining quasi-targeted metabolomics and in-depth bioinformatics - Wang, Xiaotong; Liu, Ying; Kang, Nianxin; Xu, Guojie (Frontiers in Neuroscience, 2023)
Licorice (Gan-Cao in Chinese) is one of the most famous herbal medicines around the world. The fermentation of probiotics and herbs can change the chemical constituents and significantly improve the efficacy. However, it is still unknown whether licorice fermented with probiotics would produce beneficial therapeutic effects. This study aimed to comprehensively analyze the chemical constituents in fermented licorice via quasi-targeted metabolomics, predict the potential efficacy of fermentation products via diverse bioinformatic methods, and further verify the efficacy of fermentation products through in vitro and in vivo experiments. As a result, 1435 compounds were identified totally. Among them, 424 natural medicinal products were classified with potentially important bioactivities, including 11 anthocyanins, 10 chalcones and dihydrochalcones, 25 flavanones, 45 flavones and flavonols, 117 flavonoids, 34 isoflavonoids, 21 phenols and its derivatives, 20 phenylpropanoids and polyketides, 96 terpenoids and 25 coumarins and derivatives. Interestingly, bioinformatic prediction showed that the targets of some important compounds were related to neurodegeneration, oxidoreductase activity and response to stress. In vitro and in vivo tests further verified that fermented licorice had excellent effects of DPPH clearance, anti-oxidation, anti-neurodegeneration and anti-stress. Thus, this study would provide a reference method for related research and the development of fermented licorice-related products.